THE DUALITY OF COURTLY LOVE IN THE CANTERBURY TALES: A CASE STUDY OF FATHER AND SON - Japhet Mokani (UICELL, 2021)
Scholasticism delivered dogmatic principles of love and marriage that greatly influenced medieval culture and literature. The aristocracy and the poets in medieval English strove to live and represent the circular notions of love and those established by Christian standards side by side. Medieval Christian doctrine of ancillia theologia which speculated among other things that passionate love was fraught with evil even in conjugal relationship and the Feudal marriage system in which arranged marriages downplayed the interest of the woman held sway between 1066 and 1500. Thus, medieval philosophy and education was dramatically influenced by Christian religious dogmas, and the feudal dispensation to develop and maintain Courtly Love practice in two dimensions. The two notions of love, practiced under the Courtly Love system are mutually exclusive and represent two separate worlds apart. In this two fold expression of love, the Knights, driven by their amatory and romantic affection, demonstrated through the courtly love practice that true love can actually exist outside marriage, with or without physical consummation. Geoffery Chaucer in The Canterbury Tales represents the two ideas of Courtly Love using the tales of the Knight and the Squire. The Knight’s Tale and The Squire’s Tale respectively represent the earlier conventions of medieval courtly love of Camelot and King Arthur’s court and cult, characterized by strong chivalric codes of legendary Knights, and the latter conventions of courtly love in which the Knight and lover was no longer bound by strict chivalric codes. This study explores these two courtly love dimensions as they are portrayed through these two characters in The Canterbury Tales. Keywords: Courtly Love, Knight, Squire, Ancillia Theologia, Camelot